Envisioning a socially accountable doctor: a three-axis curriculum emerging from final-year medical student reflections - Lionel Green-Thompson; Patricia McInerney; Robert Woollard (University of Johannesburg, 2018)
Social accountability in health professions education is important for the reduction of health disparities. There is a need for the development of curricula which begin to produce graduates who are responsive to community needs. These curricula need to include dialogues with communities, deep reflection and a transformative perspective. This study used a grounded theory approach to explore the perceptions of social accountability amongst final-year medical students. These students grappled with the definition of social accountability but described it as the tension between obligation and a willingness to serve. Five themes regarding social accountability were drawn from the students' feedback: 'it's poorly defined'; 'web of interconnected relationships'; 'losing my heart and losing my compassion'; 'more wide-angled view of things' and 'if I don't go there, then who will go?'. These themes are connected through relational statements of three curricular axes of reflective practice, complexity and meaningful relationships. In each of these axes, participants identified catalysts and detractors for the progressive development of an accountable medical graduate. How to cite this article: GREEN-THOMPSON, Lionel; MCINERNEY, Patricia; WOOLLARD; Robert. Envisioning a socially accountable doctor: a three-axis curriculum emerging from final-year medical student reflections Scholarship of Teaching and Learning in the South, v. 2, n. 1, p. 76-94, Apr. 2018. Available at: Available at: http://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=27 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/